Crop nutrition & fertilization management of selected tropical fruit crops and tropical industrial tree crops - Magat, Severino S.; Philippine Council for Agriculture, Forestry and Natural Resources Reseach and Development (Los Banos, Laguna Philippine Council for Agriculture, Forestry and Natural Resources Reseach and Development, 2005)
This CD-ROM contains the PDF format of the book.
Crop nutrition and fertilization management of selected tropical industrial tree crops -- Crop nutrition and fertilization management of selected tropical fruit crops.
Available also in book format.
PDF format.
Keywords: Tropical crops; Tropical fruit; Tree crops -- Tropics; Plants -- Nutrition; Fruit -- Fertilizers; Fertilizers -- Application -- Tropics